A double-blind randomized trial of hyperbaric oxygen for persistent symptoms after brain injury - Lindell K. Weaver; Rosemary Ziemnik; Kayla Deru; Antonietta A. Russo (Scientific Reports)
Abstract In this double-blind randomized trial, adults with persistent symptoms following non-stroke brain injury received 40 hyperbaric oxygen (HBO2) sessions or 40 sham sessions over 12 weeks. Three months later, all were offered 40 unblinded HBO2 sessions. Participants completed the Neurobehavioral Symptom Inventory (NSI) at baseline, 13 weeks (after 40 chamber sessions), 6 months, 9 months (after the second chamber series), and 12 months, with prime outcome at 13 weeks, and additional questionnaires, neuropsychological tests, and functional measures. We enrolled 49 participants and analyzed 47 due to drop-out/exclusion (26 males, 40 with traumatic brain injury). Baseline NSI was 35.9 ± 15.8 in the HBO2 group (n = 26) and 30.7 ± 16.9 in the sham group (n = 21) (p = 0.28). Mean 13-week change scores were 10.6 ± 10.6 (HBO2 group) and 3.6 ± 5.9 (sham group) (mean difference 7.0, 95% CI 1.7–12.3, p = 0.01). The HBO2 group improved on measures of olfaction, anxiety, sleep difficulties, and vestibular complaints. Both groups reported improvements in depression, headaches, PTSD symptoms, physical quality of life, and degree to which difficulties interfere with daily life. With an additional 40 HBO2 sessions, the original HBO2 group reported additional improvements on NSI at 12 months. Only 15 original sham participants completed the second chamber series, limiting conclusions from that data.